Desingning to decide : conceptual architecture of innovative projects proposals analysis and managerial implication - Thuillier, Antoine; Fuller, Matthew; David, Albert (HAL CCSD, 2018)
Startup companies face many challenges in the early years of their existence. During these critical stages, they must convince decision makers to provide them with critical resources, such as capital investments, support from startup incubators, or obtaining grants or subsidies.To succeed, entrepreneurs must present their fledgling businesses in an engaging and convincing way. As they create legitimacy surrounding their entrepreneurial project, they tend to bend reality by presenting their ideas as being far more developed and mature than is the case. While presenting a well-defined project hides the “fuzzy” aspects of innovation and creating a new business, it may present a risk that fixates and curtails the startup’s ability to adjust their trajectory as they move ahead.In this paper, we study a specific formalization of innovative ideas: startup pitch decks. We analyze 121 startups as they apply to enter an incubator. In this paper, we identify common trends and differences in their content and structure. We then show how a presentation’s content can be characterized using formal design theory as a descriptive language and decision-making tool by proposing a model we call “conceptual architecture”. Further analysis of interactions between entrepreneurs and the incubator’s selection committee explores the decision process as a design task that densifies the conceptual content of the pitch. We then suggest a process of systematic conceptual densification that could help both entrepreneurs and decision makers fully express the potential of an idea in terms of continued or future product development, or in some cases preparing entrepreneurs for a shift or “pivot” towards an alternative but conceptually related market.